Minimum Service Standar (MSS) For Basic Education in Musi Rawas Regency - Hartoyo, Hartoyo; Danim, Sudarwan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Implementation of Minimum Service Standard (MSS) in basic education is one of the indicators the success of development in education. Each regency with its authority carries out the program to support the Minimum Service Standard of basic education. This is important because the implementation of Minimum Service Standards of education has been become one of the main programs in regional and national development The purpose of the study was to describe how far the achievement in minimum service standards of basic education in Musi Rawas Regency in the year of 2022. The data was collected through quantitative and qualitative ways, i.e., interview, observation and documentation. It was analyzed through documentary analysis with descriptive method. The result of the study showed that the achievement of minimum service standard of basic education in Musi Rawas was 96,72% its mean in main completion category and for all aspects of minimum service standard was 94.14%. the rough participation rate for elementary school was 100.99% (students: 46,974 and the citizen 46,486). While for Junior high school the rough participation rate was 104,30% (students: 24,154 and the citizens: 23158). It means that almost all the citizens ant the age 7-12 and 13-15 attended the school. For the research method used is a descriptive method with a mixed approach. The quantitative data was analyzed descriptively and the qualitative data was analyzed through interactive model. The result of the analysis was based the newest data from official publication of the Ministry of Home Affair and The Annual Report for MSS of Education of Musi Rawas Regency